Ambiguous loss and post‐traumatic growth: Experiences of mothers whose school‐aged children were born extremely prematurely. Issue 7 (24th April 2018) - Wilson, Caroline; Cook, Catherine
Abstract : Aims and objectives: To develop insight into the experiences of mothers whose school‐aged children were born extremely prematurely. Background: Extreme prematurity, where infants are born at 28 weeks or earlier, has significant initial maternal impact in terms of distress, uncertainty and disruption to maternal identity. However, little is known about the experiences of these mothers beyond their child's infancy. Design: A qualitative study was undertaken using thematic analysis, drawing on a cluster of social constructionist theories that have been applied to studies investigating mothers' early preterm or childhood disability experiences. Methods: The study involved face‐to‐face interviews with nine mothers whose children were born prior to 28 weeks and were now aged between 4‐to‐7 years old. Results: Participants described a prolonged period of anxiety, and relative isolation due to infection fears and complex care regimes. Although they grieved their different mothering trajectory, they celebrated their children's successes and noted their own resilience. The following themes were identified: traumatic beginnings; dialectics and the horror‐miracle contradiction; labour‐intensive parenting and managing the multidisciplinary team; stigma and storying the meaning of premature birth; and impact on relationships. Conclusions: Women's vulnerability and resilience are evident long after the birth of an extremely prematurely born infant. Women value connection with similar mothers, and yet finding community is often daunting due to their children's early complex needs. Generalist healthcare providers may be unaware of the experiences these mothers have endured, and need to enquire about their well‐being. Relevance to clinical practice: The lives of mothers of extremely preterm infants may take years to merge with the world of those mothers who parent healthy, term infants. Neonatal nurses and those in primary health care are well placed to notice signs of isolation, depression and anxiety, and to support and refer women appropriately.